Euphemism of “Mangupa” in Traditional Marriage Ceremonial of Batak Mandailing - Siti Isma Sari Lubis (Politeknik Negeri Padang, 2019)
The importantce of Euphemism in speaking especially in public is done to maintain harmony in society. Euphemism itself is derived from the Greek which is eu means well and phenai means to speak. It is defined as a word or expression which is mild or indirect that substituted for one considered to be too hars or blunt when referring to something unpleasant or embarrassing (Oxford Dictionary). As we know that language and culture are two things that cannot be separated, the usage of euphemism in conversation especially in traditional ceremonial is often occurred. This paper described the euphemism in Mandailing ethnic especially for traditional ceremonial which is called as mangupa that often be done in marriage ceremonial. This research is qualitative descriptive. The source of the data is the utterances which is delivered in marriage ceremony especially in part mangupa. Data was collected by using video recording, and face to face interview to get further information from elderly with average age 50 years old until 60 years old. The data analyzed based on the types and function of euphemism by Allan and Burridge (1991). While the meaning is based on the interview with erderly. Euphemism is often used in Batak mandailing wedding ceremony especially in part mangupa. There were twenty pharase that considered as the euphemism in the mangupa utterances that has been analyed based on Allan and Burridge. While the function of the euphemism that had been identified based on the Allan and Burridgein in this study, it can be found there are only two function.